Optimalisasi Jaminan: Pemindahan Tanggung Jawab ke Pihak Ketiga - Muh. Fitra Sudarman; Saharuddin Saharuddin; Muh. Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This research investigates the transfer of collateral objects by debtors to third parties without the creditor's knowledge, examining legal implications under the Civil Code. The study finds that the transfer of land rights requires a valid Sale and Purchase Deed prepared by a Land Deed Making Officer. If the transfer is based on a flawed deed without meeting legal requirements, it is deemed null and void. Settlement efforts for such transfers can follow either the litigation or non-litigation paths. Non-litigation options involve deliberations and mediation, demonstrating an attempt to resolve legal issues outside the judicial process. In the examined cases, both parties opted for non-litigation approaches, engaging in deliberations and mediation instead of pursuing legal action.